Two new Nothophytophthora species from streams in Ireland and Northern Ireland: Nothophytophthora irlandica and N. lirii sp. nov - O'Hanlon, Richard; Destefanis, Maria; Milenković, Ivan; Tomšovský, Michal; Janoušek, Josef; Bellgard, Stanley E; Weir, Bevan S; Kudláček, Tomáš; Horta Jung, Marilia; Jung, Thomas (PloS one, 2021)
Slow growing oomycete isolates with morphological resemblance to Phytophthora were obtained from forest streams during routine monitoring for the EU quarantine forest pathogen Phytophthora ramorum in Ireland and Northern Ireland. Internal Transcribed Spacer (ITS) sequence analysis indicated that they belonged to two previously unknown species of Nothophytophthora, a recently erected sister genus of Phytophthora. Morphological and temperature-growth studies were carried out to characterise both new species. In addition, Bayesian and Maximum-Likelihood analyses of nuclear 5-loci and mitochondrial 3-loci datasets were performed to resolve the phylogenetic positions of the two new species. Both species were sterile, formed chlamydospores and partially caducous nonpapillate sporangia, and showed slower growth than any of the six known Nothophytophthora species. In all phylogenetic analyses both species formed distinct, strongly supported clades, closely related to N. chlamydospora and N. valdiviana from Chile. Based on their unique combination of morphological and physiological characters and their distinct phylogenetic positions the two new species are described as Nothophytophthora irlandica sp. nov. and N. lirii sp. nov. Their potential lifestyle and geographic origin are discussed.
Keywords: Severní Irsko; Northern Ireland; mezerníky ribozomální DNA; Rivers; sekvenční analýza DNA; řeky; Heterokontophyta; DNA, Ribosomal Spacer; Phylogeny; Phytophthora; fylogeneze; nemoci rostlin; Stramenopiles; Sequence Analysis, DNA; Plant Diseases